2012
DOI: 10.1111/j.1521-0391.2012.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Testosterone Interacts with Lifetime Physical Abuse to Predict Anger Rumination and Cognitive Flexibility among Incarcerated Methamphetamine Users

Abstract: The present pilot study hypothesized that degree of exposure to prenatal testosterone interacts with a history of lifetime physical abuse (LPA) to predict the cognitive (anger rumination) and behavioral (intimate partner and interpersonal violence) components of aggression within incarcerated methamphetamine (MA) users. In addition, we hypothesized that the degree of exposure to prenatal testosterone interacts with LPA to predict cognitive flexibility (Stroop Color-Word performance). Male inmate MA users (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…The literature search (Fig. 1 ) identified 19 partly dependent articles (Vehmas et al 2006 ; Kornhuber et al 2011 , 2013 ; Manning and Fink 2011 ; Herschl et al 2012 ; Borkowska and Pawlowski 2013 ; Romero-Martínez et al 2013 ; Park et al 2014 ; Hoskin and Ellis 2015 ; Han et al 2016 ; Canan et al 2017 , 2018 ; Lenz et al 2017 , 2018a ; Müller et al 2017 ; Cicek et al 2017 ; Hoskin 2017 ; Hobson 2018 ; Kim et al 2018 ) and 18 independent samples. Two studies (Hoskin and Ellis 2015 ; Hoskin 2017 ) are based on the same collective and, therefore, count as one independent sample in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search (Fig. 1 ) identified 19 partly dependent articles (Vehmas et al 2006 ; Kornhuber et al 2011 , 2013 ; Manning and Fink 2011 ; Herschl et al 2012 ; Borkowska and Pawlowski 2013 ; Romero-Martínez et al 2013 ; Park et al 2014 ; Hoskin and Ellis 2015 ; Han et al 2016 ; Canan et al 2017 , 2018 ; Lenz et al 2017 , 2018a ; Müller et al 2017 ; Cicek et al 2017 ; Hoskin 2017 ; Hobson 2018 ; Kim et al 2018 ) and 18 independent samples. Two studies (Hoskin and Ellis 2015 ; Hoskin 2017 ) are based on the same collective and, therefore, count as one independent sample in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on college students, an interesting investigation [13] has shown that 2D∶4D ratio correlate with psychopathy and callous affect. Investigating incarcerated methamphetamine users, others [14] have found that greater prenatal testosterone exposure, as indicated by 2D∶4D ratio, is associated with increases in anger thinking and a reduction in cognitive flexibility, at least among individuals who have experienced physical abuse [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Turanovic, Pratt, and Piquero (2017) recently published a meta-analysis of 32 studies and 361 estimates of effect size, in which they found a weak but significant effect size of the relation between 2D:4D ratio and violent criminal behavior. Within this metaanalysis, only two studies recruited samples of criminal offenders (Herschl, Highland, & McChargue, 2012a;Romero-Martínez, Lila, Catalá-Miñana, Williams, & Moya-Albiol, 2013), but without comparing them with other groups. Both coincide in reporting an association of low 2D:4D ratios with anger (Herschl, Highland, & McChargue, 2012b) and violence (Romero-Martínez et al, 2013).…”
Section: D:4d Ratio As Predictor Of Sexual and Non-sexual Violent Behaviormentioning
confidence: 99%
“…Within this metaanalysis, only two studies recruited samples of criminal offenders (Herschl, Highland, & McChargue, 2012a;Romero-Martínez, Lila, Catalá-Miñana, Williams, & Moya-Albiol, 2013), but without comparing them with other groups. Both coincide in reporting an association of low 2D:4D ratios with anger (Herschl, Highland, & McChargue, 2012b) and violence (Romero-Martínez et al, 2013). Bailey and Hurd (Bailey & Hurd, 2005), and Hönekopp and Watson (2011) report significant associations between low digit ratio and aggression (defined as ''behavior intended to harm another individual" according to Archer, 2009 cited by Hönekopp & Watson, 2011) in men but not in women, and Benderlioglu and Nelson (2004) found that 2D:4D ratio was predictive only of reactive aggression in women, but not in men.…”
Section: D:4d Ratio As Predictor Of Sexual and Non-sexual Violent Behaviormentioning
confidence: 99%